A Wireless Sensor Network for RF-Based Indoor Localization. (29th May 2008) - Kaseva Kaseva, Ville A. Ville A.; Kohvakka Kohvakka, Mikko Mikko; Kuorilehto Kuorilehto, Mauri Mauri; Hännikäinen Hännikäinen, Marko Marko; Hämäläinen Hämäläinen, Timo D. Timo D.
Abstract : An RF-based indoor localization design targeted for wireless sensor networks (WSNs) is presented. The energy-efficiency of mobile location nodes is maximized by a localization medium access control (LocMAC) protocol. For location estimation, a location resolver algorithm is introduced. It enables localization with very scarce energy and processing resources, and the utilization of simple and low-cost radio transceiver HardWare (HW) without received signal strength indicator (RSSI) support. For achieving high energy-efficiency and minimizing resource usage, LocMAC is tightly cross-layer designed with the location resolver algorithm. The presented solution is fully calibration-free and can cope with coarse grained and unreliable ranging measurements. We analyze LocMAC power consumption and show that it outperforms current state-of-the-art WSN medium access control (MAC) protocols in location node energy-efficiency. The feasibility of the proposed localization scheme is validated by experimental measurements using real resource constrained WSN node prototypes. The prototype network reaches accuracies ranging from 1 m to 7 m.With one anchor node per a typical office room, the current room of the localized node is determined with 89.7% precision.